Analisis Target dan Realisasi Penerimaan Pajak Bumi dan Bangunan di Kecamatan Tondano Selatan - Sumual, Frida Magda; Bayang, Jeane enjelia; Sumampouw, Olviane olke (Innovative: Journal Of Social Science Research, 2024)
The aim of this research is the Target and Realization of Land and Building Tax Revenue in South Tondano District. Based on the results of PBB revenue, it greatly influences Regional Original Income (PAD). South Tondano District has targets planned every year. Based on data obtained from the Minahasa Regency Regional Revenue Agency, sources of income in the land and building tax (PBB) sector have increased. However, the targets each year are not as expected by the Regional Government. The government certainly has a strong influence on the realization of land and building tax (PBB) revenues carried out in South Tondano District, in controlling Taxpayers so that it determines the level of community participation in paying land and building tax (PBB). The research approach that the author will use in the research is qualitative research, with 6 informants. Based on the results of the research and discussion in the previous chapter, it can be concluded that: 1. The realization of PBB revenue in 2023 has not yet reached the target because it has only been realized at IDR 192.563.644 with a percentage of 44.79% of the set target. 2. The level of awareness of taxpayers is not yet fully compliant because the 2023 PBB revenue target of IDR 429.929.151 has only been achieved at IDR 192.563.644 with a percentage of 44.79%. Keywords : Tax Target and Realization